Comparison of Melted Corium Relocation during Severe Accident of High Temperature Reactor using Moving Particle Semi-Implicit Method - Irfan, Muhamad; Humolungo, Ismail; Mustari, Asril Pramutadi Andi; Permana, Sidik (Physics Department, Faculty of Mathematics and Natural Sciences, University of Jember, 2023)
System failure in nuclear reactors can cause degradation of a reactor core, allowing melting and relocation of the corium to the lower plenum in the nuclear reactor system. In this study, a severe accident simulation was carried out using the Moving Particle Semi-Implicit (MPS) method. In this method, we model the relocation of molten corium on the reactor core (support plate) to the lower plenum for several conditions with variations: corium material, lower plenum conditions, temperature, viscosity, and density. Those treatments were carried out in order to be able to compare and analyze the characteristics of the corium melt by reviewing the velocity profiles. The formation of a corium pool and debris bed can result in significant temperature differences and high heat flux against the walls of the reactor vessel, causing a decrease in the integrity of the reactor vessel and reactor failure.Keywords: Corium, Uranium Dioxide (UO2), Zirconium Dioxide (ZrO2), Fluid Relocation, Moving Particle Semi-Implicit (MPS).